2019
DOI: 10.1002/polb.24820
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions of the rapid‐compression‐induced mesomorphic isotactic polypropylene under high‐pressure annealing

Abstract: The mesomorphic isotactic polypropylene was prepared by rapid compression instead of the common method of temperature quenching, and their phase transition under high pressure was investigated in depth by combining wide‐angle X‐ray diffraction, small‐angle X‐ray scattering, and differential scanning calorimetry techniques. It was found that annealing under pressure can promote the further arrangement of chain segments of the mesophase toward the crossed state in the orthorhombic γ‐phase, and the long period of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…The above circular samples were treated by compression with a home-made high pressure device shown in Figure 1a, whose detailed information has been described in previous work [21,22]. The compression treatment consists of four steps as given in Figure 1b: First, the samples were pre-pressurized at 10 MPa and heated to 200 °C, then annealed isothermally for 10 min to erase the processing histories.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above circular samples were treated by compression with a home-made high pressure device shown in Figure 1a, whose detailed information has been described in previous work [21,22]. The compression treatment consists of four steps as given in Figure 1b: First, the samples were pre-pressurized at 10 MPa and heated to 200 °C, then annealed isothermally for 10 min to erase the processing histories.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, several studies proved that pressurization is an efficient approach to prepare polymer materials with special performance, such as living polymer sulfur which exhibits exceptional thermodynamic and kinetic stability, glassy polyether-ether-ketone samples possessing excellent friction and considerable stiffness, and the glassy poly (lactic acid) which shows better cold crystallization performance [18,19,20]. Additionally, our recent work indicated the crystal structure and morphology of iPP can be accurately controlled by adjusting pressurization conditions [21], and firstly proved high pressure-annealing can induce meso-γ transformation [22]. These results above have confirmed that pressurization is a novel method to tailor the crystalline structure of iPP.…”
Section: Introductionmentioning
confidence: 99%
“…The high-pressure treatment was performed on a homemade pressure device, and the sample assembly is shown in Figure 1a, whose detailed information has been described in previous work [28,34]. The experimental pressure and temperature profiles are shown in Figure 1b.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…The specimen was placed between two aluminum plates and pressed by two opposing pistons under a desired pressure within a certain time, and the required temperature was supplied by the outer heating jacket. The experimental procedure was as follows: after loading the specimen, a relatively low pressure (10 MPa) was applied, and the sample was heated to 200 • C and annealed at this temperature for 10 min to erase processing histories; in order to ensure that the sample has solidified at the end of pressurization, the desired pressure was set at 1.7 GPa so as to obtain a sufficiently high undercooling [28,34], then the relaxed melt at 200 • C were pressurized to 1.7 GPa within the controllable durations of 2,22,34,45,113,226,453,895,1308, 2125, and 2833 s, respectively, which correspond to the wide pressurization rate ranging from 0.6-750 MPa/s; subsequently, the pressurized samples were immediately cooled down to 40 • C at an average cooling rate of about 10 • C/min under 1.7 GPa; at last, the pressure was completely released to obtain the solidified samples. For comparison, another group of samples were prepared by heated to 200 • C, annealed for 10 min, and then cooled down to 40 • C under atmospheric pressure.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…This process is known as relaxation and significantly determines the degree of orientation generated in the component during the manufacturing process and, thus, local anisotropies with respect to mechanical [ 13 , 14 ], optical [ 10 , 14 ], and shrinkage-related [ 15 ] properties. The speed of the intramolecular conformational ordering process depends on the mobility of the molecular chains and is thus determined by the free volume between the polymer chains of the amorphous melt [ 16 ]. As the free volume between the polymer chains increases with increasing temperature [ 17 ] and decreases with the orientation of the molecular chains [ 11 ], this affects the relaxation times.…”
Section: Introductionmentioning
confidence: 99%